Implementation of Information and Technology-Based Tourism Development Policy on Penyengat Island - Juzandra, Jimmy; Kurnianingsih, Fitri; Okparizan, Okparizan (Kemudi, 2024)
Penyengat Island is a developing tourist destination in Indonesia, known for its rich historical and cultural heritage. In order to further boost tourism on the island, an Information and Technology-Based Tourism Development Policy has been implemented. This policy aims to leverage the power of technology to enhance the visitor experience, promote sustainable tourism practices, and increase tourism revenue. In this study, we utilized a qualitative research method grounded in Edward III’s grounded theory approach to understand the impact of the Information and Technology-Based Tourism Development Policy on Penyengat Island. Data was collected through interviews with key stakeholders involved in implementing the policy, including government officials, local businesses, and tourists. The results of our study show that the implementation of the Information and Technology-Based Tourism Development Policy has had a positive impact on Penyengat Island. The use of technology, such as online booking systems and virtual tours, has made it easier for tourists to plan their trips and explore the island’s attractions. Additionally, the policy has helped to raise awareness of the island’s cultural heritage and promote sustainable tourism practices, such as waste management and conservation efforts. In conclusion, the Information and Technology-Based Tourism Development Policy has been successful in driving tourism development on Penyengat Island. Moving forward, continued investment in technology and sustainable tourism practices will be key to further enhancing the visitor experience and maximizing the economic benefits of tourism for the local community.